Dialkyl and Alkylene Dithiophosphate of Selenium(IV) Derivatives - A.S. El-Khaldy, Adnan; M.M. Abushanab, Alaa; M. Baraka, Rajai; A. Wasef, Marguerite (Asian Journal of Chemistry, 2016)
Selenium tetrachloride reacts with O,O-dialkyl and alkylene dithiophosphoric acids in 1 : 4 molar ratio in refluxing benzene to yield Se[S2P(OR)2]4, R = Et, Pr-n, i-Pr, i-Bu and Ph, and Se[S2POGO]4 where G = –CH2CMe2CH2–, –CH2CEt2CH2– and –CMe2CMe2–. The complexes are viscous liquids in open chain derivatives and red crystalline solids in cyclic derivatives, soluble in mixture solvents (DMSO and CHCl3) and monomeric in nature. These have been characterized on the basis of elemental analysis, molecular weight determinations, IR and multinuclear NMR (1H, 13C and 31P NMR).